2023
DOI: 10.1039/d2ra06870b
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-inflammatory, in silico molecular docking and molecular dynamics simulation of oleanane-type triterpenes from aerial parts of Mussaenda recurvata

Abstract: Two new triterpenes recurvatanes A and B were isolated from Mussaenda recurvata using bioactive-guided investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…NO inhibition of compounds 1-12 were determined with the same procedure reported previously. 21,22 Dulbecco's Modied Eagle's Medium (DMEM) contained L-glutamine (2 mM), HEPES (10 mM), sodium pyruvate (1 mM), and 10% fetal bovine serum (FBS). RAW 264.7 cells were cultured in DMEM, seeded in 96well culture plates (each well 2 × 10 5 cells), and incubated for 3 days (the tested condition: 37 °C in 5%-CO 2 humidied air).…”
Section: Measurement Of No Production Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…NO inhibition of compounds 1-12 were determined with the same procedure reported previously. 21,22 Dulbecco's Modied Eagle's Medium (DMEM) contained L-glutamine (2 mM), HEPES (10 mM), sodium pyruvate (1 mM), and 10% fetal bovine serum (FBS). RAW 264.7 cells were cultured in DMEM, seeded in 96well culture plates (each well 2 × 10 5 cells), and incubated for 3 days (the tested condition: 37 °C in 5%-CO 2 humidied air).…”
Section: Measurement Of No Production Assaymentioning
confidence: 99%
“…20 M. recurvata is thought to be a good source of anti-inammatory chemicals. 21,22 Previous research on this Vietnamese plant found nine anti-inammatory compounds: ve saponins and four oleanane-type triterpenes. 21,22 However, not much is known about Mussaenda saigonensis's chemical and biological data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation